(untitled) (Rivista Italiana di Filosofia Analitica Junior, 2018)
In this article I will criticize the so called Frankfurt-style cases. These cases have been built with the purpose of denying that in order to hold a person responsible, it’s necessary this person could have done otherwise, namely there were alternative possibilities. I present here two arguments according to which Frankfurt’s cases did not succeed in this attempt. In the first argument I will focus, from and ethical and a logical point of view, on the Principle of Alternative Possibilities, and I will show that the Frankfurt-style cases are not truly able to falsify it. The second argument is semantical and concerns the formulation of Frankfurt example.